Pengaruh Motivasi Kerja, Disiplin Kerja, dan Kepuasan Kerja terhadap Kinerja Karyawan PT Dwi Pillar Perdana - Noviyanto Noviyanto; Mauli Siagian (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
Employee performance is an important factor in achieving organizational goals, making it essential for companies to understand the factors that influence employee performance. This study aims to examine the effects of work motivation, work discipline, and job satisfaction on employee performance at PT Dwi Pillar Perdana. A quantitative research approach with a survey method was employed by distributing questionnaires to 100 employees of the company. The collected data were analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression analysis with the assistance of SPSS software. The findings indicate that work motivation, work discipline, and job satisfaction each have a positive and significant effect on employee performance. Furthermore, these three independent variables simultaneously have a significant influence on employee performance. The coefficient of determination (Adjusted R Square) of 0.944 indicates that 94.4% of the variation in employee performance can be explained by work motivation, work discipline, and job satisfaction, while the remaining 5.6% is influenced by other factors outside the research model. These findings imply that organizations should continuously improve employee motivation, strengthen work discipline, and enhance job satisfaction to achieve better employee performance and support organizational effectiveness.